Analysis of Tensile Strength of Inert Gas Metal Welding on Aluminum 5083 with Variations in Argon Gas Current and Discharge: Analisa Kekuatan Tarik Hasil Las Metal Inert Gas pada Aluminium 5083 dengan Variasi Kuat Arus dan Debit Gas Argon - Sektiawan, Hadi Bagus; Fahruddin, A'rasy (Universitas Muhammadiyah Sidoarjo, 2021)
In the technology industry, metal raw materials such as steel and aluminum have an important role in the production process, as so far there is no metal that cannot be joined by welding. Metal Inert Gas (MIG) welding method is a gas arc welding that uses a welding wire as well as an electrode. In the Metal Inert Gas (MIG) welding process, the heat from this welding process is generated by a welding arc formed between the wire electrode and the workpiece. The purpose of this study was to determine the tensile strength of the welding results in the connection process with Metal Inert Gas (MIG) against aluminum (Al) 5083 series 6 mm thick, the welding was carried out with various current strength treatments, namely 120 A, 130 A, 140 A. and Argon gas discharge 5 lt/minute, 10 lt/minute, 15 lt/minute in each welding process. This research is useful to know and understand about the analysis of the welding process on aluminum 5083 with a thickness of 6 mm with Metal Inert Gas (MIG) welding process using vertical (3 grove) welding techniques. The method used in this study is the analytical method, which is a method for testing by adding different treatments of current and discharge variations of Argon gas during the welding process of the specimen, so that different welding strengths will be obtained in each specimen.